Polymorphs, salts, and cocrystals: what's in a name? - Aitipamula, Srinivasulu; Banerjee, Rahul; Bansal, Arvind K.; Biradha, Kumar; Cheney, Miranda L.; Choudhury, Angshuman Roy; Desiraju, Gautam R.; Dikundwar, Amol G.; Dubey, Ritesh; Duggirala, Nagakiran; Ghogale, Preetam P.; Ghosh, Soumyajit; et al. (Crystal Growth & Design, 2012)
The December 2011 release of a draft United States Food and Drug Administration (FDA) guidance concerning regulatory classification of pharmaceutical cocrystals of active pharmaceutical ingredients (APIs) addressed two matters of topical interest to the crystal engineering and pharmaceutical science communities: (1) a proposed definition of cocrystals; (2) a proposed classification of pharmaceutical cocrystals as dissociable ``API-excipient'' molecular complexes. The Indo U.S. Bilateral Meeting sponsored by the Indo-U.S. Science and Technology Forum titled The Evolving Role of Solid State Chemistry in Pharmaceutical Science was held in Manesar near Delhi, India, from February 2-4, 2012. A session of the meeting was devoted to discussion of the FDA guidance draft. The debate generated strong consensus on the need to define cocrystals more broadly and to classify them like salts. It was also concluded that the diversity of API crystal forms makes it difficult to classify solid forms into three categories that are mutually exclusive. This perspective summarizes the discussion in the Indo-U.S. Bilateral Meeting and includes contributions from researchers who were not participants in the meeting.

Polymorphs, salts and cocrystals: what's in a name? (vol 12, pg 2147, 2012) - Aitipamula, Srinivasulu; Banerjee, Rahul; Bansal, Arvind K.; Biradha, Kumar; Cheney, Miranda L.; Choudhury, Angshuman Roy; Desiraju, Gautam R.; Dikundwar, Amol G.; Dubey, Ritesh; Duggirala, Nagakiran; Ghogale, Preetam P.; Ghosh, Soumyajit; et al. (Crystal Growth & Design, 2012)

Exploring novel cocrystals of milrinone: a cardioprotective drug combined with nutraceuticals and an NSAID - Kenguva, Gowtham; Rekha Rout, Smruti; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Sanphui, Palash; Dandela, Rambabu (CrystEngComm, 2024)
Milrinone is a bipyridine phosphodiesterase (PDE) inhibitor of the second generation. It's a PDE-III antagonist that raises cAMP levels to support heart function and acts as a systemic vasodilator in chronic decongested cardiovascular illness. It is categorised as class II in the Biopharmaceutics Classification System (BCS), indicating that it exhibits poor aqueous solubility and high permeability. Three new cocrystals of the cardioprotective drug milrinone (MR) with two nutraceuticals, e.g. sesamol (SES) and resveratrol (RES), and an anti-inflammatory drug, e.g. niflumic acid (NIF), were successfully synthesised using mechanochemical and solution crystallisation techniques. Thermal analysis (DSC and TGA) and diffraction tools (PXRD and SCXRD) were used to obtain structural insights into all the cocrystals. Their crystal structures indicate that the dimeric interactions in MR are preserved in the crystal structures in addition to carboxylic acid/phenol & ctdot;pyridine heterosynthons. Among the three synthesized molecular solids, MR.SES was more soluble than the native drug. The solubility of the cocrystals was correlated with polar surface contacts, the solubility of the coformer and melting points (inversely). We believe that the new MR.SES cocrystal offers a novel approach to enhance the drug's solubility, which may have a positive impact on its synergistic cardioprotective effects.

Structural insights into ketanserin salts with aliphatic acids and their physiochemical properties - Kenguva, Gowtham; Rout, Smruti Rekha; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Sanphui, Palash; Dandela, Rambabu (CRYSTENGCOMM, 2024)
Keywords: PHARMACEUTICAL COCRYSTAL; SEROTONIN; SHYDROCHLOROTHIAZIDE; solubility